For absolute equations, you actually have two equations you are solving for:
x - 1/5 = 3
and -(x - 1/5) = 3. There you have a negative outside the parentheses, that means you have to just switch the signs around in the parenthesis (aka multiply by -1).
So you would end up with -x + 1/5 = 3.
So your two equations to solve for x are:
x - 1/5 = 3 and -x + 1/5 = 3.
To solve the left equation, add 1/5 to both sides:
x = 3 + 1/5 But you need to change the fractions to get an answer.
x = 15/5 + 1/5
x = 16/5 this is your first answer.
Now solve the second equation: -x + 1/5 = 3.
It's pretty much the same thing: except you subtract 1/5 from both sides.
-x = 3 - 1/5
now change the fractions
-x = 15/5 - 1/5
-x = 14/5
x is negative (or multiplied by -1) so in order to find positive x, you need to divide both sides by -1, or just change the signs.
So you end up with:
x = 14/5
and you are done! :)